Measuring sustainability: An evaluation framework for sustainability transition experiments. Issue 103 (January 2020) - Williams, Stephen; Robinson, John
Highlights: We propose a tripartite evaluation framework that examines STE processes, societal effects, and sustainability transitions impacts. Societal effects evaluation provides information on outputs and outcomes of STEs but do not address the issue of sustainability transition. We propose a development pathway approach as a framework with which to characterize transformational societal change. Our framework assesses STEs through the lenses of STS and governance, regime rules and behaviours at multiple levels, actors and practices, and SES. The UN SDGs provide a mechanism through which to validate the comprehensiveness of conceptions of sustainability in transition impacts. Abstract: Sustainability Transition Experiments (STEs), leveraging a transdisciplinary research approach, have recently been proposed as a method to accelerate sustainability transitions. This paper outlines a proposed three-part evaluation framework to assess the process, societal effects, and sustainability transition impacts of STEs. The paper extracts the key insights from multiple literatures, generating a set of indicators to be used in assessing sustainability transition experiments. Particular emphasis is placed on the assessment of longer-term sustainability impacts. We propose a development pathway approach to organize elements of sustainability transition impact into a coherent framework that highlights the inter-relationships between levels of scales in systems transition and foregrounds the role of changes in governance roles and relationships and the role of politics in transitions. The paper offers insights into the challenge of evaluating the sustainability transition impacts of a transdisciplinary research project and provides an important bridge between the evaluation of processes, societal effects, and their link to sustainability transition impacts.